Causes of Mass Mutual Violence: Structuring Concepts and Subjective Factors of Deliberate Wars - Nikolai S. Rozov (Гуманитарный вектор)
Two definitions of war are critically examined: one classical and one modern. We show that the features emphasized in them are not necessary and sufficient. These shortcomings have been overcome in the previously proposed definition of war as ongoing mass mutual armed organized violence. A wide range of studies of the nature and causes of wars is characterized by heterogeneity of approaches, concepts, theories and levels of analysis. The ways of structuring concepts in reviews of recent years have been considered and the following simplified structure has been proposed: the actor level (subjectivity in mental orders) with decision-making processes leading to wars, the level of interactions between actors (social dynamics) with dyadic or multi-actor relations, the level of dynamics and co-evolution of orders as the encompassing context of the role of wars in world history. This article focuses only on the first level of analysis. The questions posed by contemporary scholars, relevant ideas, hypotheses, and concepts are discussed. In particular, researchers see the causes of war in false optimism in unchecked interests, in intangible incentives, in uncertainty, in commitment problems, in delusions. Much attention is paid to the role of ideologies in the readiness to go to war and mobilize forces to wage war. The distinction between fast and slow thinking of actors is used. Distortions in risk-related decision making are analyzed. Subjective factors relevant to the formation of the determination to go to war include such heterogeneous but interrelated layers of reality as hormonal background, structures of the unconscious, and ritual practices of social organization. An attempt is made to present all these very heterogeneous ideas and models in a single conceptual apparatus, including such concepts as concerns, challenges-threats and challenges-opportunities, attitudes and interactive rituals.